PENGARUH BENDING PADA ANTENA MIKROSTRIP TERHADAP GAIN, DIRECTIVITY, DAN EFFICIENCY DENGAN ORIENTASI BENDING ARAH SUMBU Y - Arifin, Muhammad Iqbal; Purnomo, Muhammad Fauzan Edy; Mustofa, Ali (Jurnal Mahasiswa TEUB, 2024)
Antennas must adapt to a time when wearable and flexible forms are necessary. The microstrip antenna may need to be bent for this purpose, which may modify its properties or specifications. In this study, a stair-like 27-star ground plane patch is used to create a microstrip antenna that operates at 2.4 GHz. CST Studio Suite 2019 software was used for design and simulation, while a signal generator and spectrum analyzer were used for measurements. The simulation findings demonstrate that bendinggenerates yield gradation in the gain, directivity, and efficiency characteristics of the microstrip antenna. The measurement results demonstrate that gain, directivity, and efficiency may be varied. The smaller the bending radius the more bent the antenna become, therefore the antenna will work differently. Keywords: Microstrip Antenna, Bending, Gain, Directivity, Efficiency